Evaluation of Antimicrobial and Healing Activities of Frog Skin on Guinea Pigs Wounds - Rezazade Bazaz, Mahere (Jundishapur J Microbiol, 2015)
BACKGROUND: Frog skin secretions have potentials against a wide spectrum of bacteria. Also, frog skin compositions have healing properties. OBJECTIVES: The aim of this study was to investigate the antibacterial potentials along with healing properties of frog skin Rana ridibunda, a species which thoroughly lives in Iran marshes, as a biological dressing on wounds. MATERIALS AND METHODS: In this study, excisional wounds, dressed with frog skin, were compared between experimental and control groups of guinea pigs. In the experimental groups, wounds were dressed with the dermal (FS) and epidermal (RFS) sides of fresh frog R. ridibunda skin, while only usual cotton gauze covered the wounds of the control group. Furthermore, microbial samples were taken on different days (0, 3, 5, and 7 days post injury) to count the number of the colony-forming units. Additionally, the microbial penetration test was performed on frog skin and then the progression of wound closure was evaluated. RESULTS: In the microbial studies, the bacterial load considerably declined in the wounds treated with FS and RFS compared with the control wounds. On day 7 post injury, the numbers of the colony-forming units for the FS, RFS, and control groups were 6.75, 105, and 375, respectively. In the penetration test, fresh frog skin showed to be a bacterial resistant dressing. The results revealed that the rate of wound closure in the experimental groups significantly was accelerated in comparison with that in the control group. CONCLUSIONS: Our results demonstrated the antimicrobial properties of frog skin as a wound dressing, which has antimicrobial effects per se. This biological dressing shows promise as an effective biological wound dressing insofar as not only is it capable of resisting microbes and accelerating wound healing but also it is cost-effective and easy to use.